2007
DOI: 10.1007/s11434-007-0327-5
|View full text |Cite
|
Sign up to set email alerts
|

Mechanism of the interaction between Au nanoparticles and polymerase in nanoparticle PCR

Abstract: Nanoparticle PCR is a novel method to optimize DNA amplification. It performs well in improving specificity, enhancing sensitivity and speed. Several mechanisms were proposed in previous studies: one was based on the interaction between gold nanoparticles (AuNPs) and DNA while the other was attributed to the heat transfer property of AuNPs. In this paper, we propose that the interaction between AuNPs and DNA polymerase can significantly influence PCR. First, the addition of DNA polymerase can eliminate the inh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
32
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 33 publications
(36 citation statements)
references
References 19 publications
4
32
0
Order By: Relevance
“…Similarly, AuNPs, which have been widely reported to enhance the specificity of PCR 10,20,26 , also showed the same manner ( Figure 5D). …”
Section: Nanomaterials Do Not Inhibit the Non-specific Amplification supporting
confidence: 63%
See 3 more Smart Citations
“…Similarly, AuNPs, which have been widely reported to enhance the specificity of PCR 10,20,26 , also showed the same manner ( Figure 5D). …”
Section: Nanomaterials Do Not Inhibit the Non-specific Amplification supporting
confidence: 63%
“…To explore more details about the inhibitory effect on PCR caused by the surface of ASMNPs, we used non-amino-modified nanoparticles as controls. A comparison of Figure 2A and Figure 2B shows that PCR was more sensitive to inhibition caused by ASMNPs than by was previously only attributed to the interaction of the nanomaterials with thermostable DNA polymerase, 26 and other components of the PCR assay mixture were not examined. In the current study, ASMNPs, which are super-paramagnetic, were used to easily identify the components of PCR that were adsorbed by nanomaterials.…”
Section: Mechanism By Which Nanomaterials Inhibit Pcrmentioning
confidence: 85%
See 2 more Smart Citations
“…As for the non-monotonic behaviour shown in Figure 4, the reduced improvement induced by AuNPs at higher concentration was probably caused by the over-binding of single-stranded of DNA by AuNPs, which leads to the agglomeration and precipitation of AuNPs [21,22]. Another study of normal PCR revealed that the concentrations of both AuNPs and polymerase influence the PCR reaction rate until fully saturated [23].…”
Section: Discussionmentioning
confidence: 95%